Meningkatkan Daya Saing UMKM Lokal melalui Strategi Pemasaran Digital di Era Digital - Vera Maria; Ahmad Fauzan Aziz; Depi Rahmawati (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research explores the implementation of digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) in an increasingly competitive digital era. Through a descriptive approach, practical steps in adopting digital marketing strategies are identified, including creating responsive websites, strategically using social media, developing quality content, SEO optimization, and data-driven marketing. The challenges faced by MSMEs in implementing these strategies are also analyzed, along with tips and tricks to overcome them. Additionally, recommendations for the government and stakeholders are presented, including policies and programs that support MSMEs in digital marketing, as well as collaboration with digital platforms and service providers. In conclusion, with the right combination of strategies and continuous support, MSMEs can leverage the full potential of digital marketing to enhance their competitiveness and growth in the digital era.